2018
DOI: 10.1111/ejn.14283
|View full text |Cite
|
Sign up to set email alerts
|

Striatal GABAergic interneuron dysfunction in the Q175 mouse model of Huntington's disease

Abstract: The pathological hallmark of Huntington's disease (HD) is the massive loss of striatal and cortical neurons. Until recently, it was believed that striatal interneurons were spared from degeneration. This view has changed after the demonstration that parvalbumin (PV)‐expressing interneurons also are vulnerable in humans. Here we compared morphological and functional changes of striatal fast‐spiking interneurons (FSIs) and low‐threshold spiking (LTS) interneurons in the Q175 mouse model of HD at presymptomatic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 70 publications
2
28
0
Order By: Relevance
“…ChR2 was selectively expressed in striatal PV- and SOM-expressing interneurons by stereotactically injecting a Cre-dependent AAV-ChR2-eYFP into WT and Q175 mice crossed with PV- and SOM-Cre mice, respectively (Figures 1A,C). Recordings from eYFP positive cells in PV-Cre (Figure 1B1) and SOM-Cre (Figure 1D1) mice showed distinct electrophysiological properties as previously reported (Tepper et al, 2010; Holley et al, 2019). Compared with SOM-expressing interneurons, PV-expressing interneurons were more hyperpolarized at rest, and displayed suprathreshold firing frequencies of 50–100 Hz.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…ChR2 was selectively expressed in striatal PV- and SOM-expressing interneurons by stereotactically injecting a Cre-dependent AAV-ChR2-eYFP into WT and Q175 mice crossed with PV- and SOM-Cre mice, respectively (Figures 1A,C). Recordings from eYFP positive cells in PV-Cre (Figure 1B1) and SOM-Cre (Figure 1D1) mice showed distinct electrophysiological properties as previously reported (Tepper et al, 2010; Holley et al, 2019). Compared with SOM-expressing interneurons, PV-expressing interneurons were more hyperpolarized at rest, and displayed suprathreshold firing frequencies of 50–100 Hz.…”
Section: Resultssupporting
confidence: 80%
“…There is growing evidence that GABA neurotransmission is abnormal in animal models of HD (Cepeda et al, 2004, 2010; Centonze et al, 2005; Andre et al, 2011; Dvorzhak et al, 2013; Indersmitten et al, 2015; Hsu et al, 2018). Further studies from our laboratory demonstrated alterations in intrinsic and synaptic properties in both FSIs and LTS interneurons which may contribute to the increased striatal GABA transmission (Cepeda et al, 2013; Holley et al, 2019). While there are multiple sources of GABA inhibition in the striatum of HD model mice, the underlying mechanisms are not well understood.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to SPNs, most local interneurons are relatively spared in HD, with the exception of PV interneurons, which are reduced in numbers in human patients and R6/2 mice (Giampà et al, 2009;Reiner et al, 2013;Reiner and Deng, 2018). A detailed analysis of PV cells in the zQ175 mouse model furthermore uncovered changes in morphology, physiological properties, and connectivity (Holley et al, 2019a). A recent study combining activity manipulation of PV interneurons with simultaneous calcium imaging of PV cells and SPNs in freely moving mice pointed to the function of PV cells in facilitating execution of movement (Gritton et al, 2019); it is therefore tempting to speculate that dysfunction and loss of striatal PV interneurons may play a causal role in HD-related akinesia, a hypothesis still to be tested in HD model animals.…”
Section: Basal Ganglia Circuitsmentioning
confidence: 99%